Effect of Cu-nanoparticles versus Cu-salt in Enchytraeus albidus (Oligochaeta): differential gene expression through microarray analysis - Gomes, Susana I. L. (2019)
Despite increased utilization of copper (Cu) nanoparticles, their behaviour and effect in the environment is largely unknown. Enchytraeids are extensively used in studies of soil ecotoxicology. Ecotoxicogenomic tools have shown to be valuable in nanotoxicity interpretation. A cDNA microarray for Enchytraeus albidus has recently been developed, which was used in this study. We compared the gene expression profiles of E. albidus when exposed to Cu-salt (CuCl(2)) and Cu-nanoparticles (Cu-NP) spiked soil. Exposure time was 48 h with a concentration range of 400 to 1000 mg Cu/kg. There were more down-regulated than up-regulated genes. The number of differently expressed genes (DEG) decreased with increasing concentration for CuCl(2) exposure, whereas for Cu-NP, the number did not change. The number of common DEG decreased with increasing concentration. Differences were mainly related to transcripts involved in energy metabolism (e.g. monosaccharide transporting ATPase, NADH dehydrogenase subunit 1, cytochrome c). Overall, our results indicated that Cu-salt and Cu-NP exposure induced different gene responses. Indirect estimates of Cu-NP related ion-release indicated little or no free Cu(2+) activity in soil solutions. Hence, it was concluded that the Cu-NP effects were probably caused by the nanoparticles themselves and not by released ions.